Veno-arterial extracorporeal membrane oxygenation: an overview of different cannulation techniques - Banfi, Carlo; Pozzi, Matteo; Brunner, Marie-Eve; Rigamonti, Fabio; Murith, Nicolas; Mugnai, Damiano; Obadia, Jean-Francois; Bendjelid, Karim; Giraud, Raphaël (Journal of Thoracic Disease, 2016)
Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) has known a widespread application over the last decade and is now an effective and valuable therapeutic option in refractory cardiogenic shock of various etiologies. In this subgroup of critically ill and unstable patients in cardiogenic shock, VA-ECMO allows, on the one hand, temporary hemodynamic stabilization with improvement of end-organ function and, on the other hand, gives the time to perform complementary diagnostic exams and to decide the therapeutic strategy in these high-risk candidates for immediate long-term mechanical circulatory support (MCS) implantation. VA-ECMO could also be suggested as a rescue therapeutic option for refractory cardiac arrest. It showed promising results in the specific setting of in-hospital cardiac arrest and survival rates with good neurological outcome are reported between 20% and 40%. Conversely, there are contrasting data in the literature about survival after VA-ECMO for out-of-hospital cardiac arrest, as results are highly dependent on low-flow time. The aim of the present report is to offer an overview of different cannulation techniques of VA-ECMO.